High Power <g transform="matrix(1.25,0,0,-1.25,0,19.7)"> <g transform="translate(72,-56.24)"> <text transform="matrix(1,0,0,-1,-71.95,56.29)"> <tspan style="font-size: 17.93px; " x="0" y="0">T</tspan> <tspan style="font-size: 17.93px; " x="10.957063" y="0">m</tspan> </text> <text transform="matrix(1,0,0,-1,-47.04,63.46)"> <tspan style="font-size: 12.55px; " x="0" y="0">3</tspan> <tspan style="font-size: 12.55px; " x="6.2765002" y="0">+</tspan> </text> </g> </g> -Doped Fiber Lasers Tuned by a Variable Reflective Output Coupler - Tang, Yulong; Yang, Yong; Xu, Jianqiu (Research Letters in Optics, 2008)
Wide wavelength tuning by a variable reflective output coupler is demonstrated in high-power double-clad Tm3+-doped silica fiber lasers diode-pumped at ∼790 nm. Varying the output coupling from 96% to 5%, the laser wavelength is tuned over a range of 106 nm from 1949 to 2055 nm. The output power exceeds 20 W over 90-nm range and the maximum output power is 32 W at 1949 nm for 51-W launched pump power, corresponding to a slope efficiency of ∼70%. Assisted with different fiber lengths, the tuning range is expanded to 240 nm from 1866 to 2107 nm with the output power larger than 10 W.